The Effect of Project-Based Learning Through Teaching Performance on Students’ learning achievement of English for mathematics - Syarifa Rafiqa; Ridwan Ridwan; Rustam Effendy Simamora (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This study aims to determine student learning outcomes by using a project-based learning model. One learning model that can improve student learning outcomes with teaching performance can use project-based learning. The research method uses pre-experimental with a one-shot case study design. The determination of the sample used a purposive sampling method with 29 students in the English for mathematics class at the Borneo University of Tarakan. The data collection used the post-test instrument which was then analyzed using the one-sample t-test. The results of the analysis show 7,489 > 4,060, with a sig. 0.001 < 0.05, it can be concluded that there are significant differences in student English for mathematics achievement using project-based learning (PBL). The results showed that there was an effect of the project-based learning model on student achievement in English for mathematics classes at Borneo Tarakan University.